Confocal Laser Endomicroscopy for Diagnosing Malignant Pleural Effusions - Zirlik, Sabine; Hildner, Kai; Rieker, Ralf; Neurath, Markus; Fuchs, Florian; Vieth, Michael (Medical Science Monitor, 2018)
BACKGROUND Confocal laser endomicroscopy (CLE) enables "in vivo" microscopic tissue diagnosis based on tissue reflectance or tissue fluorescence upon application of fluorescence agents. The aim of the present study was to evaluate CLE as a new diagnostic approach for differentiation between malignant versus non-malignant pleural effusions. MATERIAL AND METHODS In 100 patients with pleural effusions, thoracentesis was performed. Cresyl violet and acriflavine were used as contrast agents for probe-based CLE of effusions. CLE video sequences were assessed by 4 independent investigators (2 experienced in this technique, 2 with only basic knowledge). In addition, all CLE samples were evaluated by an expert pathologist (p). Results were compared with conventional cytology of effusions and histology of cell blocks. RESULTS CLE reliably permitted identification of malignant cells in pleural effusions. Sensitivity for detection of malignant effusions was 87% (p: 87%) and 81% (p: 72%) for acriflavine and cresyl violet, respectively. With regard to specificity, acriflavine and cresyl violet yielded a mean value of 99% (p: 100%) and 92% (p: 100%). CONCLUSIONS In this pilot study, CLE permitted simple and rapid detection of malignant pleural effusions. Larger prospective studies are warranted to corroborate our findings.
EVALuna2:35147